Effects of nitric oxide on magnocellular neurons of the supraoptic nucleus involve multiple mechanisms - Silva,M.P. da (2014)
Physiological evidence indicates that the supraoptic nucleus (SON) is an important region for integrating information related to homeostasis of body fluids. Located bilaterally to the optic chiasm, this nucleus is composed of magnocellular neurosecretory cells (MNCs) responsible for the synthesis and release of vasopressin and oxytocin to the neurohypophysis. At the cellular level, the control of vasopressin and oxytocin release is directly linked to the firing frequency of MNCs. In general, we can say that the excitability of these cells can be controlled via two distinct mechanisms: 1) the intrinsic membrane properties of the MNCs themselves and 2) synaptic input from circumventricular organs that contain osmosensitive neurons. It has also been demonstrated that MNCs are sensitive to osmotic stimuli in the physiological range. Therefore, the study of their intrinsic membrane properties became imperative to explain the osmosensitivity of MNCs. In addition to this, the discovery that several neurotransmitters and neuropeptides can modulate their electrical activity greatly increased our knowledge about the role played by the MNCs in fluid homeostasis. In particular, nitric oxide (NO) may be an important player in fluid balance homeostasis, because it has been demonstrated that the enzyme responsible for its production has an increased activity following a hypertonic stimulation of the system. At the cellular level, NO has been shown to change the electrical excitability of MNCs. Therefore, in this review, we focus on some important points concerning nitrergic modulation of the neuroendocrine system, particularly the effects of NO on the SON.